Treatment of diaphyseal pathological fractures in children with monostotic fibrous dysplasia using cortical strut allografts and internal plating: A retrospective clinical study. Issue 5 (February 2019) - Zhang, Peng; Kang, Liangqi; Hu, Qimiao; Xia, Chenjie; Yu, Huan; Wang, Lei; Lian, Kejian; Lin, Dasheng
Abstract : Abstract: Children with fibrous dysplasia (FD) chronically suffer from pain, pathological fractures, and limb deformities. The most effective methods for managing the associated pathological fractures remain controversial. The purpose of this study was to evaluate the clinical results of the treatment of diaphyseal pathological fractures in children with monostotic fibrous dysplasia (MFD) using cortical strut allografts and internal plating. We retrospectively analyzed outcomes in nine children (5 boys, 4 girls) with diaphyseal pathological fractures due to MFD, who were treated with cortical strut allografts and internal plating (6 femoral fractures and 3 humeral fractures) between July 2007 and November 2012. The median age of patients in our study was 10 years (range 6–14 years). The fracture healing time, pain, extremity function, refracture, graft resorption, and complications were recorded to evaluate treatment effects. The median time of follow-up was 69 months (range 60–75 months). All patients had good postoperative fracture healing with a median healing time of 14 weeks (range 12–16 weeks). None experienced refracture, graft resorption, nerve injury, or limitation of extremity function or other complications. The fixation remained stable in all patients, with no evidence of loosening screws after surgery. In pediatric patients, the described surgical approach is an effective and reliable treatment method for diaphyseal pathological fractures caused by MFD. Cortical strut allografts, which act as biological bone plates, can provide good mechanical support while increasing the rate of fracture union.